Otocinclus batmani, a new species of hypoptopomatine catfish (Siluriformes: Loricariidae) from Colombia and Peru - Lehmann A.,Pablo (2006)
A new species of the hypoptopomatine catfish genus Otocinclus is described from two localities in the upper Río Amazonas basin: a tributary of the Río Puré in Colombia and two tributaries to the Río Amazonas near Iquitos in Peru. The new taxon can be easily distinguished from all congeners, except Otocinclus cocama, by having a single, intensely pigmented, vertical W-shaped caudal fin spot and by having three discrete dark bands on dorsum, between the dorsal-fin base and the caudal fin. Otocinclus batmani differs from O. cocama by the absence of vertically elongated blotches from the dorsal midline to the ventral border of flanks, and by lacking a posterior extension of black pigmentation on the base of two central caudal-fin rays. Phylogenetic relationships of the new species are investigated and it is possibly more closely related to a clade formed by O. huaorani, O. mariae, O. bororo, O. mura, and O. cocama.